1996
DOI: 10.1002/(sici)1099-0496(199602)21:2<90::aid-ppul5>3.0.co;2-t
|View full text |Cite
|
Sign up to set email alerts
|

Distribution and transmission ofPseudomonas aeruginosa andBurkholderia cepacia in a hospital ward

Abstract: Genotyping and antibiotic susceptibility testing were used to analyze Pseudomonas aeruginosa and Burkholderia cepacia strains from sink drain from 14 pediatric patients with cystic fibrosis (CF) and from hospital personnel as part of a 4 week prospective study of strain transmission in a pediatric ward. A total of 87.5% of all washbasin drains were contaminated with P. aeruginosa [102 to 105 colony forming units (CFU)/ml sink fluid], whereas B. cepacia was found only once in a sink drain. From the eight CF pat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
99
0

Year Published

2002
2002
2017
2017

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 118 publications
(101 citation statements)
references
References 14 publications
2
99
0
Order By: Relevance
“…(5%), and 4% Salmonella typhi (Table 1). Doring (1996) and Aiello et al (2004), observed the incidence of S.aureus, B.subtilis, E.coli, Lactobacillus, Enterobacter sp., K.pneumoniae, and Pseudomonas sp. on human palms.…”
Section: Resultsmentioning
confidence: 98%
“…(5%), and 4% Salmonella typhi (Table 1). Doring (1996) and Aiello et al (2004), observed the incidence of S.aureus, B.subtilis, E.coli, Lactobacillus, Enterobacter sp., K.pneumoniae, and Pseudomonas sp. on human palms.…”
Section: Resultsmentioning
confidence: 98%
“…This ability was stated by Fryklund et al 27 who concluded that most Gramnegative bacteria survive on the hands for 1 hour or more. Moreover, the study of Döring et al 28 …”
Section: Discussionmentioning
confidence: 99%
“…145 Furthermore, Doring and colleagues showed that Pseudomonas aeruginosa and Burkholderia cepacia were transmissible by handshaking for up to 30 minutes when the organisms were suspended in saline, and up to 180 minutes when they were suspended in sputum. 146 The study by Islam and colleagues with Shigella dysenteriae type 1 showed its capacity to survive on hands for up to 1 hour. 147 HCWs who have hand dermatitis may remain colonized for prolonged time periods.…”
Section: Organism Survival On Handsmentioning
confidence: 99%